The coconut, a renewable resource for the design of green materials (2019)
The need to reduce environmental degradationhas led, nowadays, to the search for less polluting materials.Colombia has a large area suitable for cultivation of differentplant species, which belong essentially to the food industry.Some parts of these plants may be used in engineering. This isthe case of the coconut palm, which could be properly grown inabout 70,000 hectares of Colombia, and its fruit can be entirelyused. The coconut fruit has a hard shell or endocarp, which, dueto its hardness, is suitable for being used as reinforcement incomposite materials. Eco-composites offer good properties anda lower environmental impact, because they are biodegradableand renewable.